Investigating the Link between Early Life and Breast Anomalies - Panagiotis Christopoulos; Alkis Matsas; Makarios Eleftheriades; Georgia Kotsira; Anna Eleftheriades; Nikolaos F. Vlahos (MDPI AG, 2023)
Several factors during childhood and adolescence are thought to be associated with the development of proliferative benign breast diseases and breast cancer in adulthood. In order to identify them, the authors conducted an extensive review of the literature up to October 2022, searching for clinical studies, reports, and guidelines in English. A thorough Medline/Pubmed and Google scholar database research was performed, investigating the link between diet, exercise, age of menarche, body mass index, ionizing radiation exposure during childhood and adolescence, and proliferative breast diseases and breast cancer in adulthood. A list of keywords, including breast disorders, adolescence, childhood, and breast cancer was included in our search algorithm. Numerous studies concede that the development of breast disease in adulthood is influenced by various risk factors, whose influence begins during early childhood and adolescence.